Constitutional self-government - Eisgruber, Christopher L. (Harvard University Press, 2001)
The author focuses directly on the Constitution's seemingly undemocratic features. He argues that constitutionalism is best regarded not as a constraint upon self-government, but as a crucial ingredient in a complex, non-majoritarian form of democracy.